1992
DOI: 10.1073/pnas.89.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic copolymer 1 inhibits human T-cell lines specific for myelin basic protein.

Abstract: Copolymer 1 (Cop 1) is a synthetic basic random copolymer of amino acids that has been shown to be effective in suppression of experimental allergic encephalomyelitis and has been proposed as a candidate drug for multiple sclerosis. Cop 1 is immunologically cross reactive with myelin basic protein (BP) and was shown to inhibit murine BP-specific T-cell lines of various H-2 restrictions. In the present study these findings were extended to include human T-cell lines. Cop 1 competitively inhibited the proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 38 publications
3
47
0
Order By: Relevance
“…31). With respect to the binding of GA to immune cells, in vitro experiments have shown that GA binds promiscuously to class II MHC (32)(33)(34), thereby competing with MBP-derived peptides for the MBP-specific TCR (35)(36)(37). This is an implausible setting in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31). With respect to the binding of GA to immune cells, in vitro experiments have shown that GA binds promiscuously to class II MHC (32)(33)(34), thereby competing with MBP-derived peptides for the MBP-specific TCR (35)(36)(37). This is an implausible setting in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…GA has been shown to bind promiscuously to class II MHC molecules in vitro (32)(33)(34), thus competing with MBP-derived peptides for the MBP-specific TCR (35)(36)(37). Interestingly, GA induces a Th1 to Th2 shift accompanied by the production of the anti-inflammatory cytokine IL-10 both in vitro and in vivo (34, 38 -44).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…Although its mechanism of action is not completely known, its inhibition of central nervous system myelin antigens by competing as an MHC ligand may be of importance (20)(21)(22). The ability to stimulate proliferation of Th2 over Th1 cells, suppressing T-cell activity is also of relevance as well (23).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that a random polymer of amino acids with common MHC and TCR contact residues containing frequent spacer, nonbulky amino acids might act as a universal peptide Ag, engaging the TCR in such a manner that the proliferation of many T cells are induced. In this regard, T cell lines and clones with reactivity to GA in vitro have been generated from rats, mice, and other animal species primarily on immunization of the animals with the Ag (10). Interestingly, in retrospect a study using PBMCs from healthy control subjects showed a strong proliferative and IFN-␄ response to GA (22).…”
mentioning
confidence: 99%